2015
DOI: 10.1002/app.42171
|View full text |Cite
|
Sign up to set email alerts
|

Significance of polymer on emulsion stability in surfactant‐polymer flooding

Abstract: The influence of polymer on stability and shear rate on droplet size of emulsion is evaluated in the laboratory, microstructure of the emulsion is observed under a microscope, and the pore distribution of the cores is analyzed through mercury injection experiments. In the process of surfactant-polymer (SP) flooding, the thickness of polymer absorbed on the surface of the rock is calculated by a mathematical model. The experiments show that the polymer is good for the stability of emulsion, with the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…46 Degradation of polymers is crucial for polymer flooding to improve crude oil recovery, because polymer degradation decreases polymer solution viscosity and leads to an increase in water-oil viscosity ratio, thus seriously impacting polymer flooding effectiveness. 47,48 The researchers investigated polymer degradation under static conditions and different reservoir conditions. 49,50 These studies were mainly based on xanthan gum and polyacrylamide, and the results showed that the viscosity was only a little higher than that of water after mechanical shear degradation.…”
Section: Introductionmentioning
confidence: 99%
“…46 Degradation of polymers is crucial for polymer flooding to improve crude oil recovery, because polymer degradation decreases polymer solution viscosity and leads to an increase in water-oil viscosity ratio, thus seriously impacting polymer flooding effectiveness. 47,48 The researchers investigated polymer degradation under static conditions and different reservoir conditions. 49,50 These studies were mainly based on xanthan gum and polyacrylamide, and the results showed that the viscosity was only a little higher than that of water after mechanical shear degradation.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, after these two stages of oil recovery, more than 50% of the crude oil is waiting to be developed. 11,12 Therefore, a tertiary oil recovery technology called chemical flooding, which has a higher oil recovery efficiency than primary oil recovery and secondary oil recovery, is gradually emerging. 13,14 It includes thermal flooding, gas flooding, and chemical flooding.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the alkali solution penetrated into the crude oil and formed a W/O emulsion with the crude oil, which reduced the flow capacity of the water phase and increased the sweep efficiency. In 2015, Xuan 17 studied the effect of polymers on emulsion stability in poly-surface binary composite flooding. The polymer was found to be beneficial to the stability of the emulsion.…”
Section: Introductionmentioning
confidence: 99%